(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Guillain Barre Syndrome (GBS) is an acute post infectious immune mediated disorder of peripheral nerve with a marked variation in pathology, clinical presentation and prognosis. Electrophysiology has an important role in early diagnosis, electrophysiological patterns and prediction of prognosis. Objective: The aim of the study is to evaluate the electrophysiological pattern of Guillain Barre Syndrome (GBS) among our patients. Materials and methods: An observational, descriptive study was carried out in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from March, 2011 to September, 2012. Total 80 patients of GBS were recruited as the study population considering the inclusion and exclusion criteria. On the basis of nerve conduction study, patients were classified into different groups: (1) acute inflammatory demyelinating polyneuropathy (AIDP) pattern with sensory nerve conduction abnormalities (motor-sensory AIDP), (2) acute inflammatory demyelinating polyneuropathy (AIDP) pattern without sensory nerve conduction abnormalities (motor AIDP), (3) acute motor axonal neuropathy (AMAN), (4) acute motor sensory axonal neuropathy (AMSAN). Results: The range of our patients were between 18 to 68 years and 62.5% were male and 37.5% were female. Among 80 patients that are finally included in the study 50% were AMAN, 27.5% were motorAIDP, 12.5% were motor-sensory AIDP and 10% were AMSAN varieties. According to the nerve conduction study acute motor axonal neuropathy (AMAN) was the predominant subtype. In axonal form of GBS (AMAN), the compound muscle action potential (CMAP) amplitude was more than 80% of lower limit of the normal in at least two motor nerves and in AMSAN the compound muscle action potential (CMAP) amplitude was more than 80% of lower limit of the normal in at least two motor nerves and sensory nerve action potential (SNAP) amplitude was more than 80% of lower limit of the normal in at least two sensory nerves. The characteristic findings supportive of acute inflammatory demyelinating polyradiculoneuropathy include prolonged distal motor latencies (>110% of upper limit of normal), reduced conduction velocities (<90% of lower limit of normal), conduction blocks at non-entrapment sites, temporal dispersion and prolonged F wave latencies(>120% of upper limit of normal). Conclusion: This study demonstrated a higher proportion of axonal form of GBS in our country.